(untitled) (Eurasian Journal of Philology Science and Education, 2026)
This article provides a comprehensive account of the emotional and pragmatic functions of anaphora and epiphora in the poetic structure of Kazakh heroic epics. The study aims to determine the role of anaphora/epiphora in organizing epic pathos and rhythm, as well as in reader reception (emotional resonance, memorability, persuasion). Representative excerpts from epic texts were selected as material and subjected to poetic–stylistic analysis; methodologically, an open-ended survey was administered and respondents’ free-text answers were thematically coded. The findings demonstrate that anaphora, through line-initial repetition, intensifies the opening impulse and produces a “leadership voice” effect, while epiphora, via line-final formulas, consolidates the message and prolongs emotional impact. Repetition enhances textual cohesion, rhythm, and euphony, creating mnemonic salience: in the survey, lines with repetition were described as “unforgettable” and “turning into slogans.” Bringing together theoretical and empirical evidence shows that anaphora / epiphora serve as key instruments for activating national-cultural codes (spirit, unity, perseverance). The practical significance of the study lies in the systematic use of reception data in epic analysis; methodologically, it lays a foundation for future digital text analysis (positional–frequency analysis, automatic tagging based on rhythmic markers). Limitations include sample size and stratification parameters; future research should incorporate experimental designs and test the reception of repeated structures in translation through comparative assessment. Keywords: anaphora, epiphora, poetic repetition, heroic epics, emotional impact, rhythm and intonation, linguopragmatics.